Roles and Actions That Should Be Taken by The Parties In The War In Concerning Wound and Sick Or Dead During War or After War Under The Geneva Convention 1949 - Sudika Mangku, Dewa Gede (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Modern international humanitarian law consists of two historical streams: The Law of The Hague which in the past was referred to as the law of war proper, and Geneva Law or Humanitarian Law. The two schools are named after the venue for the international conferences drafting treaties on war and conflict, especially the Hague Conventions 1899 and 1907 and the Geneva Conventions, which were drafted for the first time in 1863. Both Hague Law and Geneva Law are branches from jus in bello, namely international law regarding acceptable practices in the conduct of war and armed conflict). The result of the writing of this article is that basically the scope of the First Geneva Convention in the context of scale provides protection in international and non-international conflicts, but the basis for non-international protection is not specifically explained in this convention, because in this First Geneva Convention. Non-international conflicts are only included in the General Provisions Chapter, and will be further clarified in Protocol II. This non-international scope is described in accordance with the First Geneva Convention Chapter I - General Provisions Article 3 regarding armed conflicts that are not international (non-international) taking place within the territory of one of the High Contracting Parties so that each Party to the conflict is obliged to implement the provisions applicable. The roles and actions that must be taken by the disputing parties during the war or not for the wounded and sick or dead cannot be separated from Human Rights, which must care for fellow human beings and please help regardless of ethnicity, religion, race, gender, age and skin. But in the Geneva convention only provides actions that should be done, there are no sanctions imposed if we ignore or do not comply with this Geneva convention. The method used in this research is normative juridical.